2017
DOI: 10.1093/humupd/dmx009
|View full text |Cite
|
Sign up to set email alerts
|

What factors hinder the decision-making process for women with cancer and contemplating fertility preservation treatment?

Abstract: This review has found that a wide range of internal and external factors impact the FP decision-making process. Key external issues related to current service delivery such as the provision and timing of FP information, and lack of referral from oncology to the fertility clinic. However, internal issues such as women's fears concerning the perceived risks associated with pursuing FP also hindered decision-making but these 'risks' were typically overestimated and non-evidence based. These findings suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 74 publications
2
83
0
1
Order By: Relevance
“…This aspect is obviously of great importance concerning cancer treatment, but it may be even more important for the patient. Studies have found that one of the biggest concerns for patients with malignant diseases is the time from cancer diagnosis to the initiation of treatment, as well as the concern for FP . Hence, minimizing the interval between FP‐referral and FP is not merely a matter of treatment demand, but also of great value to the psychological well‐being of the patients who are juggling thoughts of survival and the wish for future motherhood.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect is obviously of great importance concerning cancer treatment, but it may be even more important for the patient. Studies have found that one of the biggest concerns for patients with malignant diseases is the time from cancer diagnosis to the initiation of treatment, as well as the concern for FP . Hence, minimizing the interval between FP‐referral and FP is not merely a matter of treatment demand, but also of great value to the psychological well‐being of the patients who are juggling thoughts of survival and the wish for future motherhood.…”
Section: Discussionmentioning
confidence: 99%
“…As healthcare has shifted over recent decades from a paternalistic approach to a shared decision‐making approach, tools are being developed to aid patients and their families when deciding upon options. In young adult survivors, studies have shown that fertility ranks highly among patients’ concerns, and adolescents have a strong desire to participate in decisions related to their cancer and treatment . This must be taken into account by clinicians when discussing future reproductive health with children and young adults at the time of diagnosis of cancer and at later stages in their cancer journey including through adult survivorship.…”
Section: Fertility Preservationmentioning
confidence: 99%
“…Fertility counseling is more often received by women who are younger, have lower parity, a higher educational level, higher income, non‐Hispanic white ethnicity, and insurance coverage . Among women who do receive counseling, lower use of fertility preservation has been associated with concerns about cost, treatment delay, and/or an adverse impact on their cancer treatment . In prior studies of reproductive‐age women diagnosed with cancer who wanted to retain their fertility, approximately 40% to 50% of women did not use fertility preservation …”
Section: Introductionmentioning
confidence: 99%